Analisis Pengendalian Risiko Kecelakaan Kerja dengan Metode HIRARC pada Pengelolaan Limbah Medis Rumah Sakit Kelas B di Kabupaten Sidoarjo - Naniek Ratni Juliardi A. R.; Awaluddin Ilmi Nur Prasetya (Prosiding ESEC, 2022)
Hospitals as service facilities in the health sector are obliged to implement K3 guidance, this effort is carried out to avoid the risk of accidents and occupational diseas. The purpose of this study is to provide control of the risk of work accidents in the medical waste management process at the class B hospital in Sidoarjo District. This study uses observational analysis with an inductive analysis approach and the data is processed using the HIRARC method. The results show that in the medical waste management process, there are 4 potential risks with low risk values with sources of danger including slipping, exposure to liquid medical waste, and electric shock. As well as 11 potential risks with moderate risk values with sources of danger including Needle Stick Injury, exposure to blood/body fluids, skin/eye irritation, respiratory problems, sprains, and hot work area temperatures. For risk control efforts, there are 3 risk control suggestions based on the risk control hierarchy, namely Personal Protective Equipment (PPE), Administrative Control, and Technical Control.